2007
DOI: 10.1016/j.imavis.2006.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Kernel-based distance metric learning for content-based image retrieval

Abstract: For a specific set of features chosen for representing images, the performance of a content-based image retrieval (CBIR) system depends critically on the similarity or dissimilarity measure used. Instead of manually choosing a distance function in advance, a more promising approach is to learn a good distance function from data automatically. In this paper, we propose a kernel approach to improve the retrieval performance of CBIR systems by learning a distance metric based on pairwise constraints between image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 22 publications
(34 reference statements)
0
28
0
Order By: Relevance
“…As another direction, we will incorporate dissimilarity constraints into the methods to further improve the metric learning performance. Moreover, we will explore the application of the proposed methods to other real-world problems such as content-based image retrieval [7], [8], [9].…”
Section: Discussionmentioning
confidence: 99%
“…As another direction, we will incorporate dissimilarity constraints into the methods to further improve the metric learning performance. Moreover, we will explore the application of the proposed methods to other real-world problems such as content-based image retrieval [7], [8], [9].…”
Section: Discussionmentioning
confidence: 99%
“…DML methods can be used to find a linear transformation that projects the image features to a new meaningful feature space to reduce this semantic gap. Previous work showed that appropriately designed distance metrics could improve CBIR performance compared with Euclidean distance [27]. For the BoW model, the semantic meaning of visual words is ambiguous; thus, the retrieval performance can be improved by embedding the semantic information to BoW representation by supervised DML.…”
Section: Bag-of-visual-words Representation Of Lesionsmentioning
confidence: 99%
“…Multiple regression analysis is widely used since it can weight each feature, but "distance metric learning [14]" (DML) is more effective since it can take side information into account. Many studies on DML have demonstrated its usefulness in applications such as image retrieval [15], music retrieval [16], and sentence retrieval [17]. This technique can realize speaker selection if the side information is set properly.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DML has also been used for feature space transformation in a number of studies. For instance, [15] used transformation of the original image space for image retrieval. In this paper, since the perceptual voice quality similarity is used as the side information, DML can be considered to be transformation from acoustic feature space to perceptual voice quality similarity space.…”
Section: Introductionmentioning
confidence: 99%